Bioactive compounds of Marine Red algae Portieria hornemannii and its bio control effects against Culex quinquefasciatus Dengue vectors (Journal of Pharmaceutical Negative Results, 2022)
The red seaweed Portieria hornemannii was investigated for phytochemicals, yield of extract, and total flavonoids and phenol content. Methanol and chloroform were used to extract metabolites from P. hornemannii. Methanol extract from P. hornemannii (MEPH) performed superior to chloroform in the phytochemical test. Purified by 86%, the crude methanol extract is subjected to a quantitative method, which determined its total phenol content as (1.60±0.13 mg.GAE/g) and flavonoids as (1.302±0.4 mg.GAE/g). MEPH GC-MS analysis revealed 20 compounds, including n-hexadeconic acid (Rt-27.385; peak area 41.88%) and 9, 12, Octadecadienoic acid (Z, Z) (Rt-29.879; peak area-19.49%). ABTS and hydroxyl radical scavenging assays showed increased activity based on MEPH concentration. Among the three mosquito larvae tested, only Culex quinquefasciatus proved highly sensitive (100 % mortality), with LC50 and LC90 values of 2.476 and 13.207 ppm. Finally, P. hornemannii may also be considered for application as a biocontrol agent and a nutraceutical in the future.